Regional seminar on enhancing women's participation in cooperative activities ; Report and papers, Kandy, Sri Lanka, 9th to 30th September, 1980 - International Cooperative Alliance (New Delhi, 1981)
It is the view of the present writer, that the focus on women has been most timely and opportune and it certainly acts as a starting point of revitalisation to a movement which was drifting in the doldrums. Those associated with the history of cooperative development in Asia are aware that with increasing interest on centralised planning for development, many of the governments in the developing countries viewed the cooperatives as a useful instrument for the achievement of accelerated deve lopment. In the process of involving the cooperatives in this developmental effort, however, governments, policy-makers, politicians, bureaucrats and bankers began to play an increas ingly dominating and controlling role, relegating the member to the backwoods of indifference and apathy. In many situa tions, today, to many a member, the cooperative society no longer is his cooperative society, but is an extended arm of government, often a social welfare arm, through which various assistance programmes are worked out-his own role, and his own decision making power in the cooperative, have been gradually diffused. He is only at the receiving end with no demands on him to make a contribution-save perhaps to repay the loans when he can. It is, therefore, in my view, a boon to the cooperative movements, that the increasing focus on women provides a rallying point for the revitalisation of the move ment. If the model used by the Project has been able to moti vate and involve an increasing number of women in cooperative activity and if the effort has led to an increasing inner strength and a greater cohesiveness in the society, then it is quite clear that the model with suitable adaptations can be used and should be used to motivate the now apathetic and indifferent 'man' member towards greater involvement and greater participation. The project activities themselves have been subjected to two evaluations-one an internal evaluation and another by a team consisting of representatives from the donor agencies and both speak positively about the achievements and the possibilities. If, therefore this Regional Seminar has helped in any way to provide an example for action by focussing attention on the project in Sri Lanka and has shown the possibilities and has motivated at least some towards further action, then we would have achieved at least some of our objectives. We believe that in a period of member apathy and member indifference, the project provides useful experiences which can be used not only with reference to women, but also elsewhere.
Keywords: Cooperation